Multi-Agent Path-Finding and Algorithmic Graph Theory (Student Abstract) - Fairbairn, David (Proceedings of the International Symposium on Combinatorial Search, 2023)
I specialise in conducting research in Multi-Agent Path-Finding (MAPF) and Algorithmic Graph Theory. Specifically,I investigate the impact of geometric constraints ona given instance of MAPF, as well as the expansion ofMAPF to include resource constraints, target assignmentpath-finding (TAPF), and academic problems that are relevantto industry. In Algorithmic Graph Theory, I extend thecapabilities of standard and novel MAPF solvers to temporalgraphs, and explore clustering techniques and ideas thatutilise Graph Classifications on MAPF domains to reducethe computational complexity of MAPF. Furthermore, I researchthe implementation and application of massively parallelizedcomputing techniques on MAPF, especially in relationto distance matrix computation and parallelized centralizedMAPF.Aside from my PhD research, I have the pleasure to collaboratewith researchers at Tharsus Limited, to directly applymy research to novel industrial problems and developbenchmarks that are relevant to both the industry and the researchcommunity for Multi-Agent Systems.